ChemInform Abstract: Evaluating New Chemistry to Drive Molecular Discovery: Fit for Purpose?. Issue 49 (17th November 2016) - Foley, Daniel J.; Nelson, Adam; Marsden, Stephen P.
Abstract: Review: [33 refs.